Goji berries (Lycium barbarum) extract as new potential cosmetic ingredient – A first screening - Silva, Joana (2024)
Currently there is greater concern about appearance and skin care products. Although cosmetic products are not associated with serious health problems, there are concerns related to undesirable effects due to the presence of potentially carcinogenic and allergenic ingredients. Thus, consumers have been increasingly looking for products of natural and plant-based origin. The use of these products is expected to increase exponentially, and studies are urgently needed to introduce new products into the market. Goji berry is a fruit with increasing popularity due to its richness in phenolic compounds, carotenoids, organic acids, carbohydrates, and vitamins. Its antioxidant, antimicrobial and anticancer activities make this product promising for cosmetic applications. The aim of this study was to study an ecological extract obtained from goji berries through ultrasound-assisted extraction as a new ingredient incorporated into a cosmetic formulation. Goji berry extract was obtained by ultrasound-assisted extraction, according to Silva et al. . To assess safety, in vitro assays were carried out on skin cell lines. Subsequently, several cosmetic formulations incorporating the extract were developed and characterized. The results demonstrated that goji berries have no toxicity on skin cell lines. Cosmetic formulations containing the goji berries extract demonstrated to be suitable for application to the skin and maintained their characteristics during the storage period. Goji berries extract is safe and stable in cosmetic formulations, proving to be suitable for consumer needs.